2011
DOI: 10.4028/www.scientific.net/amr.308-310.167
|View full text |Cite
|
Sign up to set email alerts
|

Subsystems Change Ranking Methodology (SCRaM) for Complex Product Redesign Process

Abstract: Product redesign is hardly a straightforward process, especially for complex products. The existence of intricate interrelationships between different components of product design architecture makes it more susceptible to change propagation phenomenon. In this case, redesign risk is not easy to predict since the change effects are being propagated to other components from the initiating change component. Because of this condition, choosing the right initiating change component is essential to control redesign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In order to demonstrate the implementation feasibility and practicality of a new proposed design framework, a sample application case study is commonly used. For instances, Romli et al [49] illustrated potential use of their proposed new subsystems change ranking methodology (SCRaM) for complex product redesign process through an aircraft case study while Zhang et al [50] showed the feasibility of their proposed design framework using sample smart train case study. In line with this standard practice, a s imple validation experiment case study using the proposed IQM design framework is conducted with a few volunteering undergraduate students.…”
Section: 3simple Validation Studymentioning
confidence: 99%
“…In order to demonstrate the implementation feasibility and practicality of a new proposed design framework, a sample application case study is commonly used. For instances, Romli et al [49] illustrated potential use of their proposed new subsystems change ranking methodology (SCRaM) for complex product redesign process through an aircraft case study while Zhang et al [50] showed the feasibility of their proposed design framework using sample smart train case study. In line with this standard practice, a s imple validation experiment case study using the proposed IQM design framework is conducted with a few volunteering undergraduate students.…”
Section: 3simple Validation Studymentioning
confidence: 99%
“…Repeated changes can reduce the capacity of components to absorb changes. This means susceptibility to propagating change can only be determined statistically [16] [17], and in the end each change requires its own propagation analysis, which depends critically on knowledge of the operating margins of each component [13].…”
Section: Impact Of Change Ordersmentioning
confidence: 99%